2015
DOI: 10.1007/s00221-015-4297-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of tDCS over a delayed response inhibition task by targeting the right inferior frontal gyrus and right dorsolateral prefrontal cortex

Abstract: Many situations in our everyday life call for a mechanism deputed to outright stop an ongoing course of action. This behavioral inhibition ability, known as response stopping, is often impaired in psychiatric conditions characterized by impulsivity and poor inhibitory control. Transcranial direct current stimulation (tDCS) has recently been proposed as a tool for modulating response stopping in such clinical populations, and previous studies in healthy humans have already shown that this noninvasive brain stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
86
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 52 publications
(91 reference statements)
9
86
4
Order By: Relevance
“…Previous studies have found that anodal stimulation of the rIFG resulted in a shorter SSRT, an index of efficient response inhibition (Campanella et al 2017;Jacobson et al 2011;Jacobson et al 2012a, b;Stramaccia et al 2015). The current study did not replicate this finding.…”
Section: Discussioncontrasting
confidence: 81%
“…Previous studies have found that anodal stimulation of the rIFG resulted in a shorter SSRT, an index of efficient response inhibition (Campanella et al 2017;Jacobson et al 2011;Jacobson et al 2012a, b;Stramaccia et al 2015). The current study did not replicate this finding.…”
Section: Discussioncontrasting
confidence: 81%
“…tDCS neuromodulation of various targets has been increasingly applied in treatment research (e.g., to relieve major depression Meron et al, 2015), but it has also been used for experimental manipulation of neural networks to enhance or diminish specific cognitive functions or symptoms, including impulsivity. Anodal tDCS applied to the rIFG appears to reduce behavioral impulsivity (Cai et al, 2016; Cunillera et al, 2014; Ditye et al, 2012; Stramaccia et al, 2015), whereas anodal tDCS to the left OFC has been found to lead to a reduction in cognitive impulsivity (Ouellet et al, 2015). If behavioral and cognitive impulsivity are implicated in short-term risk for self-injurious thoughts and behaviors, tDCS may therefore have potential to become a new protocol for addressing these clinical outcomes, through targeting the respective underlying neural circuitry of these facets of impulsivity.…”
Section: Discussionmentioning
confidence: 95%
“…A concern in tDCS research is that its effects are not due to one electrode only but by the combination of effects between two electrodes (anode and cathode polarity) with potentially opposite characteristics. This has been the case with most of the studies exploring the effects of tDCS on response inhibition (Stramaccia et al, 2015). …”
Section: Introductionmentioning
confidence: 91%
“…Several neuroimaging studies have supported this association by suggesting that the right inferior frontal gyrus (IFG) has a key role on the mediation of response inhibition (Aron et al, 2004; Garavan et al, 2006; Garavan et al, 1999; Kelly et al, 2004). Furthermore, studies using anodal transcranial direct current stimulation (tDCS) to the right IFG were able to increase response inhibition in stop signal tasks (Cunillera et al, 2014; Ditye et al, 2012; Hogeveen et al, 2016; Jacobson et al, 2011; Stramaccia et al, 2015). However, it is still unclear whether IFG control on proactive control involved in response inhibition is truly a lateralized function (i.e., left IFG would have a minimal impact) or if it depends on the successful mediation between right and left IFG.…”
Section: Introductionmentioning
confidence: 99%